Perfect scoundrels (Heist society novel, 3,, 2013)
When feisty teenaged thief Kat's on-again off-again boyfriend, Hale, suddenly inherits his family's billion dollar company, Kat gets a tip-off that the will is a fake.

The downstairs girl (Tantor Media, Inc., Putnam/G.P. Putnam's Sons, Penguin Young Readers Group, 2019)
"1890, Atlanta. By day, seventeen-year-old Jo Kuan works as a lady's maid for the cruel Caroline Payne, the daughter of one of the wealthiest men in Atlanta. But by night, Jo moonlights as the pseudonymous author of a newspaper advice column for 'the genteel Southern lady'"--

The brothers Hawthorne (The Inheritance Games, ,, 2023)
"Jameson and Grayson Hawthorne are each pulled into a different high-stakes game, where they must decide who they want to be and what they will sacrifice to win"--

Heist society (Brilliance Audio on compact disc, ,, 2011)
A group of teenagers uses their combined talents to re-steal several priceless paintings and save fifteen-year-old Kat Bishop's father, himself an international art thief, from a vengeful collector.

Uncommon criminals: a Heist society novel (Heist society novel), 2,, 2011)
Fifteen-year-old Kat Bishop and her fellow talented teenagers work together to find and steal the "Cleopatra Emerald" from an unscrupulous dealer and return it to its rightful owner, while a former love of her Uncle Eddie tries to get the gem for herself.